PENGUKURAN KINERJA KEUANGAN MENGGUNAKAN ANALISIS RASIO AKTIVITAS PADA PT WAHANA SEMESTA BANYUMAS - Anggar, Anastasia; Tyas, Karunia Zuraidaning; Sepriati (Perwira Journal of Economics & Business, 2024)
Financial performance is one of the most important things in a company-related business world, both internally and externally. In assessing the performance of a company, financial reports are one of the keys. From this element of financial statements, company management can carry out a financial ratio analysis. One of the ratios used in conducting the analysis is the activity ratio. The activity ratio is used to measure the efficiency level of the utilization of the company's resources or to assess the company's ability to carry out its activities Based on the results of the calculation of the activity ratio at PT. Wahana Semesta Banyumas shows that there has been an increase in several types of ratios from 2021 to 2022, but the results achieved are still below industry standards which shows that the company's performance is still not good compared to other similar industries. This needs to be the vigilance of the company to continuously improve performance and have high competitiveness.